The social profitability of rural roads in a small open economy: do urban agglomeration economies matter? - Bell, Clive (Working paper, 2020)
In the presence of agglomeration economies, the effects of a rural roads programme depend not only on the reduction in transportation costs, but also on the form of labour mobility. When financed by a poll tax on rural households, the wage will rise, accompanied by some return migration, provided both cross-price effects in production and consumption and agglomeration economies are sufficiently small. With empirically plausible elasticities of agglomeration economies, urban households may be worse off. A tax on exports provides a countervailing distortion, yielding them some relief, yet with rather small adverse effects on rural households. If mobility takes the form of rural-urban commuting, cheaper fares will promote the exploitation of agglomeration economies. An export tax may then improve urban welfare. Using the change in the value, at producer prices, of the rural sector's net supply vector as the measure of the programme's social profitability can yield serious errors.
Keywords: Graue Literatur